2021
DOI: 10.1080/03623319.2021.1874176
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception and COVID-19 preventive behaviors: application of the integrative model of behavioral prediction

Abstract: Preventing the COVID-19 outbreak primarily depends on individuals' willingness to adopt social distancing and mask wearing behaviors. However, little is known about what drives individuals to adopt these behaviors. Guided by the Integrative Model of Behavioral Prediction, this study surveyed 590 adults in the US during the early stages of the outbreak to identify factors influencing intentions to practice social distancing and wear masks. Structural equation modeling results show that while attitudes are posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…The recent literature has demonstrated the significance of the three TPB components in predicting a series of preventive behaviors for COVID-19. For example, Duong et al [ 38 ] found that citizens’ attitudes exerted a positive and significant effect on both social distancing behavior and mask wearing behavior in the U.S. Chen and Chen [ 39 ] found that attitudes and subjective norms had a significant and positive influence on individuals’ preventive behaviors for COVID-19 among 1591 residents in China. Prasetyo et al [ 22 ] revealed the positive impacts of the three TPB variables on the intention to follow preventive measures for COVID-19 in a sample in the Philippines.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…The recent literature has demonstrated the significance of the three TPB components in predicting a series of preventive behaviors for COVID-19. For example, Duong et al [ 38 ] found that citizens’ attitudes exerted a positive and significant effect on both social distancing behavior and mask wearing behavior in the U.S. Chen and Chen [ 39 ] found that attitudes and subjective norms had a significant and positive influence on individuals’ preventive behaviors for COVID-19 among 1591 residents in China. Prasetyo et al [ 22 ] revealed the positive impacts of the three TPB variables on the intention to follow preventive measures for COVID-19 in a sample in the Philippines.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Behavioral studies have adopted different conceptual frameworks (e.g., References [7][8][9]) to illustrate the relationship between different types of risk perception and prevention measures of infectious diseases. Risk perception is generally defined as subjective judgments of a negative outcome associated with a risk [10], including different dimensions, such as cognitive, emotional, affective, personal, and societal risk perceptions [11,12]. Controlled for different individual variables, the results generally suggested that a high-risk perception of a disease is associated with an increased likelihood of practicing certain health behaviors [12].…”
Section: Introductionmentioning
confidence: 99%
“…Risk perception is generally defined as subjective judgments of a negative outcome associated with a risk [10], including different dimensions, such as cognitive, emotional, affective, personal, and societal risk perceptions [11,12]. Controlled for different individual variables, the results generally suggested that a high-risk perception of a disease is associated with an increased likelihood of practicing certain health behaviors [12]. In spatial and geographical sciences, it is well-recognized that human mobility is crucial in shaping disease transmission [13][14][15] To understand the factors shaping the mobility-related prevention of an infectious disease, studies have revealed that a higher risk perception is associated with reduced mobility [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that facemasks are widely perceived by the general public as the most efficacious preventive measure against the COVID-19 virus, serving as a strong “psychological symbol” or an effective form of protection against the anxiety imposed by the pandemic (e.g., Duong et al, 2021 ; Guo et al, 2020 ) . The alleviation of anxiety symptoms related to COVID-19 is critical for the disease prevention efforts.…”
Section: Discussionmentioning
confidence: 99%